2002
DOI: 10.1536/jhj.43.307
|View full text |Cite
|
Sign up to set email alerts
|

New Protocol to Detect Coronary Spastic Angina without Fixed Stenosis.

Abstract: SUMMARYA new combined test, accelerated exercise following mild hyperventilation (HV), was examined to determine whether it is effective at detecting a positive response in patients with pharmacologically-induced coronary vasospasm and near normal coronary arteries.Fifty-eight consecutive patients who underwent both triple non-invasive spasm provocation tests and diagnostic coronary angiography were enrolled. They all had pharmacologically-induced coronary vasospasms and no significant organic stenosis. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The new combined protocol, which consisted of 5 min of mild hyperventilation with a frequency of 24 breaths/min to 40 breaths/min followed by the modified treadmill exercise test accelerated every minute of Bruce's protocol, was the most useful method to obtain the positive rate [10]. In 58 patients with CSA without fixed stenosis, the positive frequency by the new combined protocol (63%) was significantly higher than the standard treadmill exercise test (26%) or hyperventilation test (16%), as shown in Figure 1 [12]. In contrast, we obtained the significantly higher positive response by the new combined protocol (84%) than that by standard treadmill exercise test (40%) or hyperventilation test (16%) in 40 patients with fixed stenosis and coronary artery spasm, as shown in Figure 1 [11].…”
Section: Combined Accelerated Exercise Just After the Hyperventilatiomentioning
confidence: 94%
See 1 more Smart Citation
“…The new combined protocol, which consisted of 5 min of mild hyperventilation with a frequency of 24 breaths/min to 40 breaths/min followed by the modified treadmill exercise test accelerated every minute of Bruce's protocol, was the most useful method to obtain the positive rate [10]. In 58 patients with CSA without fixed stenosis, the positive frequency by the new combined protocol (63%) was significantly higher than the standard treadmill exercise test (26%) or hyperventilation test (16%), as shown in Figure 1 [12]. In contrast, we obtained the significantly higher positive response by the new combined protocol (84%) than that by standard treadmill exercise test (40%) or hyperventilation test (16%) in 40 patients with fixed stenosis and coronary artery spasm, as shown in Figure 1 [11].…”
Section: Combined Accelerated Exercise Just After the Hyperventilatiomentioning
confidence: 94%
“…However, before performing the coronary angiography, it may be prefered by cardiologists to obtain ischemic findings in these patients. As a non-invasive examination treadmill exercise test, hyperventilation test and cold pressor test were employed for the induction of ischemia due to coronary artery spasm [4][5][6][7][8][9][10][11][12][13]. In patients with ischemic heart disease and obstructed coronary artery disease, treadmill/bicycle exercise tests are very useful to obtain the pathologic findings, whenever it may be difficult to obtain the ischemic findings to perform treadmill exercise tests in patients with coronary spastic angina (CSA) and non-obstructed coronary artery disease.…”
Section: Introductionmentioning
confidence: 99%
“…Positive coronary spasm induced by provocation tests is defined as ≥ 99% luminal narrowing 9,10,12,24,25) because the key to a diagnosis of VSA is to document a severe ischemic attack, such as ST-segment elevation. Here, we demonstrated that critical coronary spasms with TIMI 3 grade flow are associated with altered myocardial fatty acid metabolism.…”
Section: I-bmipp Findingsmentioning
confidence: 99%
“…Non-invasive tests as well as invasive testing are employed as diagnostic methods. Treadmill exercise tests, hyperventilation tests, and cold stress tests are used for the induction of ischemia due to coronary artery spasm as a non-invasive examination [3][4][5][6][7][8][9][10][11][12][13][14][15]. In patients with ischemic heart disease and obstructed coronary artery disease, treadmill exercise tests are useful to obtain the pathologic findings; however, they may not be so useful to detect the ischemic findings in patients with CSA and nonobstructed coronary artery disease.…”
Section: Introductionmentioning
confidence: 99%